A influência da paisagem na forma e no tamanho da asa de três espécies de Euglossini (Hymenoptera; Apidae) - Ribeiro, Mariléa Gonçalves (2017)
This work has aimed to evaluate the size and shape of the wing of individuals of three Euglossini bee species (Euglossa cordata (Linnaeus, 1758), Euglossa ignita Smith, 1874 and Eulaema atleticana Nemésio, 2009). For that, geometric morphometrics methods, as well as landscape metrics, were used for such evaluation. The analyzed specimens were collected in five areas, being four forest areas and one area of Agroforestry System (SAF). Morphometric analyzis were started with the right wing photograph of the individuals of each species and with the determination of anatomical landmarks and semilandmarks. Subsequently, the Cartesian coordinates obtained were used for analysis of variance of the shape and size of the wing of the populations. The results of the shape analysis were significant for the three species (p<0.05) and demonstrated that the individuals collected within the SAF area have had the greatest divergences in the shape of the wing. On the other hand, size differences were significant only for the populations of E. ignita (ANOVA: F = 5.923 and p = 0.00045). For E. cordata and El. Atleticana, there has been a significant correlation between morphometric data and landscape metrics (r<0.05), which shows a close relationship between these species and the forest cover. Thus, the present work underlines the importance of Euglossini bees in environmental quality monitoring studies, since morphometrics differences may reveal the existence of environmental stress.